Studi Etnografi pada Budaya Organisasi Rumah Ibadat Pasca Covid-19 - Cherubim, Daniel Jehuda; Loisa, Riris (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
When the covid-19 pandemic hit, synagogues had a hard time surviving. The ban on activities outside the home made the synagogue deserted and was forced to find ways to adapt to survive, one of which was the church. to adapt to survive, one of which is the church. The church management was forced to find ways for the congregation to be able to worship even though it is done at home. This gave birth to a new culture in the church organization that formed and became a post-covid-19 habit. This research uses a qualitative approach with ethnographic methods. Data collection techniques with using interview techniques. Culture in post-covid-19 church organizations is characterized by new habits that never existed before covid-19. that never existed before covid-19. Worship routines have changed due to online worship. The board's desire to communicate has changed slightly because communication during covid-19 is carried out online which is likely to cause minor conflicts. online which is likely to cause little conflict. In the leadership of church organizations In the leadership of church organizations, a culture of active leaders is formed to be able to maximize message delivery. As a result of the Covid-19 pandemic also requires church administrators to have new abilities in order to conduct church activities online. Cultural differences in the church that arise in The new management is a culture of communication that is more open to all administrators and congregations, culture that applies the habit of speaking according to valid data, as well as a mentoring culture that forms skills in church management. shaping skills in church management. Pandemi covid-19 melanda, rumah ibadat mengalami kesulitan untuk bertahan. Larangan untuk melakukan kegiatan di luar rumah membuat rumah ibadat sepi dan terpaksa harus bisa mencari cara agar beradaptasi untuk bertahan, salah satunya gereja. Pengurus gereja terpaksa harus mencari cara untuk jemaat tetap bisa beribadah walaupun dilakukan di rumah. Hal tersebut melahirkan budaya baru dalam organisasi gereja yang terbentuk dan menjadi kebiasaan pasca covid-19. Penelitian ini menggunakan pendekatan kualitatif dengan metode etnografi. Teknik pengumpulan data dengan menggunakan teknik wawancara. Budaya dalam organisasi gereja pasca covid-19 bercirikan kebiasaan baru yang tidak pernah ada sebelum covid-19. Rutinitas ibadah berubah karena adanya ibadah daring. Hasrat pengurus dalam berkomunikasi sedikit berubah karena komunikasi selama covid-19 dilakukan secara daring yang kemungkinan dapat menimbulkan konflik kecil. Dalam kepemimpinan organisasi gereja, budaya pemimpin aktif terbentuk untuk bisa memaksimalkan penyampaian pesan. Akibat pandemi Covid-19 juga menuntut pengurus gereja untuk memiliki kemampuan baru agar bisa melakukan kegiatan gereja secara daring. Perbedaan budaya dalam gereja yang timbul dalam kepengurusan baru yaitu budaya komunikasi yang lebih terbuka kepada seluruh pengurus dan jemaat,budaya yang menerapkan kebiasaan berbicara sesuai data yang valid, serta budaya mentoring yang membentuk keterampilan dalam kepengurusan gereja.